2017
DOI: 10.1007/s12026-017-8924-0
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 and CASP1 gene polymorphisms are associated with developing of acute coronary syndrome: a case-control study

Abstract: The protein products of NLRP3 and CASP1 genes are involved in the cleavage of pro-IL-1B and pro-IL-18 leading to the active cytokines, which play an important role in the development of the acute coronary syndrome (ACS). The aim of the present study was to evaluate whether NLRP3 and CASP1 gene polymorphisms are biomarkers of ACS susceptibility in Mexican population. Two polymorphisms of the CASP1 gene [G+7/in6A (rs501192) and A10370-G Exon-6 (rs580253)] and one of the NLRP3 gene [UTR'3 G37562-C (rs10754558)] w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Whereas the SNP rs4986790 in TLR4 gene that affects the extracellular domain of the receptor, and results in a decreased response to damage molecular patterns has been identified as a protective variant for hypertension in individuals with coronary heart disease (30). Additionally, other SNPs in NLRP3 and CASP1 genes have also been associated with an increased risk of atherosclerosis in different populations (31,32). Several variants in the genes involved in the innate immune response (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the SNP rs4986790 in TLR4 gene that affects the extracellular domain of the receptor, and results in a decreased response to damage molecular patterns has been identified as a protective variant for hypertension in individuals with coronary heart disease (30). Additionally, other SNPs in NLRP3 and CASP1 genes have also been associated with an increased risk of atherosclerosis in different populations (31,32). Several variants in the genes involved in the innate immune response (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found the NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome play an important role in the development of cardiovascular diseases9., 10.. Several molecular signaling pathways are shown to mediate the activation of the NLRP3 inflammasome, such as releasing of reactive oxygen species (ROS), lysosome leakage and activation of cathepsin B or the modifications in K + efflux11., 12., 13., 14., 15., 16.. Then the activation of NLRP3 inflammasome triggers a series of downstream inflammatory factors, leading to vascular endothelial dysfunction and the ultimate occurrence or development of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…CASP1 is a pro‐inflammatory factor that plays an important role in tumorigenesis by accelerating the process of apoptosis (Gonzalez‐Pacheco et al, 2017). Upregulated CASP1 expression has been earlier identified in GBM tissues (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%